The effect of family-centered empowerment model on primary caregivers of elderly patients with maintenance hemodialysis (以家庭为中心的赋权模式对老年维持性血液透析患者主要照顾者的影响) - ZHANG Wei (张卫); LI Aijuan (李爱娟); ZHAO Xiaoqiao (赵晓巧) (中西医结合护理)
Objective To explore the effect of family-centered empowerment model(FCEM)interventions on perceived stress, positive feelings and quality of life in primary caregivers of elderly patients with maintenance hemodialysis(MHD). Methods Totally 62 elderly maintenance hemodialysis patients admitted to the Blood Purification Center of the Hospital from June 2023 to December 2023 were selected as the study subjects and were randomly divided into control group (n=31) and observation group (n=31) according to the random number method. The control group adopted the routine nursing during the treatment. The observation group was given the family-centered empowerment model care program based on the routine nursing. Perceived stress, positive perception, and quality of life of primary caregivers were compared between the two groups. Results There was no significant difference in scores of Perceived Stress Scale (PSS-14), Positive Aspects of Caregiving(PAC) and Adult Carer Quality of Life Questionnaire (AC-QoL) before intervention(P＞0. 05). At three months after intervention, the score of PSS-14 in the observation group was lower than that in the control group(P＜0. 01), and scores of PAC and AC-QoL in the observation group were higher than those in the control group(P＜0. 01). Conclusion The FCEM can reduce the perceived stress of primary caregivers in elderly MHD patients, improve the positive perception of primary caregivers, and enable them to actively control their lives, and thus improve the quality of life of caregivers. (目的 探讨以家庭为中心赋权模式干预对老年维持性血液透析患者主要照顾者知觉压力、积极感受及生活质量的影响。方法 选取2023年6月—12月在东部战区总医院血液净化中心规律透析治疗的62例老年维持性血液透析患者主要照顾者作为研究对象, 按照随机数字表法随机分为对照组(n=31)和观察组(n=31)。对照组采用常规护理方法; 观察组在常规护理方案的基础上, 实施以家庭为中心赋权模式护理方案。比较两组的知觉压力、积极感受度、生活质量。结果 干预前, 两组照顾者知觉压力量表(PSS-14)、照顾者积极感受量表(PAC)和成人照护者生活质量问卷(AC-QoL)评分比较, 差异无统计学意义(P＞0. 05)。干预3个月后, 观察组照顾者PSS-14量表评分低于对照组, PAC量表和AC-QoL量表评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 以家庭为中心赋权模式能够降低老年维持性血液透析患者主要照顾者知觉压力, 提高主要照护者的积极感受度, 使其能够积极控制自己的生活, 进而提高照顾者生活质量。)